Pengembangan Taman Berdasarkan Konsep Healing Garden : (Kasus: Taman Bunga Merjosari Kota Malang) - Cahyani, Nur; Agus Setyono, Deni; Dwi Purnamasari, Wulan (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2023)
Lowokwaru District is a district that has a relatively high number of COVID-19 cases in Malang City. According to data from May 29, 2022, Malang City had 28,793 positive cases of COVID-19, while in Lowokwaru District, there were 6,583 positive cases or 23% of positive COVID-19 cases in Malang City. Merjosari Flower Park, as an active garden, can be an alternative to help speed up the healing process. However, several problems were found that could cause discomfort for visitors visiting the park, including minimal shade, noise coming from high vehicle volumes, and unpleasant odors coming from the Dinoyo Waste Disposal Site. This research aims to develop a garden based on the healing garden concept at Taman Bunga Merjosari. The development concept was generated through Kano analysis. Kano analysis is used to categorize and determine priority attributes determined by visitors. The results of this research are in the form of development concepts for each priority attribute. The development concept takes the form of providing five attributes, providing various functions for three attributes, and improving the quality of three attributes in accordance with the healing garden concept.